Jonah a VeggieTales movie - Big Idea Productions; Artisan Entertainment (Firm) (Santa Monica, CA : Artisan Entertainment, 2002)
Bob the Tomato, Larry the Cucumber and the rest of the VeggieTales gang retell the story of Jonah.
MPAA rating: G.
DVD, stereo.
Closed-captioned.
Keywords: Jonah -- (Biblical prophet) -- Juvenile drama; Bible. -- Juvenile drama; Vegetables -- Juvenile drama; Children's films; Animated films; Feature films; Video recordings for hard of hearing people